Stock authorizations: A sequential equilibrium analysis - Noe, T; Jayaraman, N (1991)
We develop a sequential equilibrium model of the common stock authorization process. We provide conditions under which actions that increase the number of slack shares, such as stock authorizations, generate negative announcement effects.